Benthic hydroids (Cnidaria: Hydrozoa) from off George V Coast (East Antarctica) - Cantero, Álvaro L. Peña; Marzal, Marina Fresneda (Zootaxa, 2018)
Hydrozoans are one of the main and most characteristic zoological groups of Antarctic benthic communities, yet there are Antarctic areas where the hydrozoan fauna is completely unknown or scarcely known as off George V Coast (East Antarctica). Hitherto, only two studies have dealt with hydroids from this area and only 16 species have been reported. The present study contributes to increase knowledge of the benthic hydroid fauna off George V Coast by studying material collected during a sampling survey associated with the CEAMARC project. A total of 12 species of benthic hydroids were found. Anthoathecata is only represented by Bimeria corynopsis, the remaining species, including Schizotricha auroraaustralis sp. nov., belong to Leptothecata. Seven of the 12 species found in the study represent new records for the area; therefore, the number of benthic hydroids known off George V Coast is raised to 23. Staurotheca is the most speciose genus, represented by three species, followed by Schizotricha with two; the remaining genera are each represented by a single species. All species are restricted to Antarctic or Antarctic/sub-Antarctic waters. Nine species (75%) are endemic to the Antarctic region, most with a circum-Antarctic distribution (7 species); only two are endemic to East Antarctica. Three species are also distributed in sub-Antarctic waters.